L’Influence de la Théorie de L’Experiencing de Eugene T. Gendlin sur L’Approche Centrée sur Le Client, de Carl R. Rogers - Richard, Marc; Turgeon, Pierre-Paul (Canadian Journal of Counselling and Psychotherapy, 2012)
Carl Rogers' theoretical approach to counselling is very often associated with the concepts of non-directiveness or the reflection of feelings. In effect, Rogers himself has spent more than thirty years devoting himself to research. As well, the strength of his theory has resulted in many investigations. Recently De La Puente and Hart have suggested a chronological developmental sequence within his theory: a non-directiveness phase, a reflection of feelings phase, and finally the experiencing phase.The purpose of this paper is to clearly show that the passage from phase two to phase three occurred primarily as a result of Eugene Gondlin's theory ofexperiencing.